2010
DOI: 10.1002/cyto.a.20965
|View full text |Cite
|
Sign up to set email alerts
|

Single cell phospho‐specific flow cytometry can detect dynamic changes of phospho‐Stat1 level in lung cancer cells

Abstract: Single cell phospho-specific flow cytometry (SCPFC) enables the investigation of signaling network interactions and the categorization of disease outcome. While this method has been successfully used to study hematologic disorders, its application on solid tumors has not been examined. This study aimed to demonstrate the ability of SCPFC to detect dynamic changes of Tyrosine phospho-Stat1 (pStat1) in solid tumor models and in human tumor samples. In the human lung cancer cell line PC14PE6/ AS2, the fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Recently, it has been demonstrated that flow cytometry can generate qualitative results concerning dose responses and kinetics of signaling molecules similar and complementary to the data obtained with blotting techniques (19,(26)(27)(28). Flow cytometry does not require a purification of the basophils.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, it has been demonstrated that flow cytometry can generate qualitative results concerning dose responses and kinetics of signaling molecules similar and complementary to the data obtained with blotting techniques (19,(26)(27)(28). Flow cytometry does not require a purification of the basophils.…”
Section: Discussionmentioning
confidence: 84%
“…Flow cytometry enables the determination of phosphorylation events in heterogeneous cell populations by co-staining cell populations with phospho-specific antibodies and antibodies for immunophenotyping (Chow et al, 2005; Lin et al, 2010; Perez et al, 2004). A caveat of conventional flow cytometry is the inability to determine the intracellular origin of a measured signal which may be especially relevant when studying signaling events.…”
Section: Introductionmentioning
confidence: 99%
“…Although the utility of SCNP assay has been well demonstrated in hematologic malignancies (5,8,9), to date, its application to solid tumors has not been widely studied, with the exception of a limited number of studies focused on lung cancer (10). Although the utility of SCNP assay has been well demonstrated in hematologic malignancies (5,8,9), to date, its application to solid tumors has not been widely studied, with the exception of a limited number of studies focused on lung cancer (10).…”
mentioning
confidence: 99%
“…Studies in hematologic malignancies have shown the value of quantitatively measuring single cell signaling networks under modulated conditions as a basis for the development of prognostic and predictive tests. Although the utility of SCNP assay has been well demonstrated in hematologic malignancies (5,8,9), to date, its application to solid tumors has not been widely studied, with the exception of a limited number of studies focused on lung cancer (10). The primary reason for this discrepancy is essentially preanalytic.…”
mentioning
confidence: 99%